2006
DOI: 10.1093/ajcn/84.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Content of redox-active compounds (ie, antioxidants) in foods consumed in the United States

Abstract: This ranked antioxidant food table provides a useful tool for investigations into the possible health benefit of dietary antioxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
332
0
17

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 522 publications
(371 citation statements)
references
References 50 publications
15
332
0
17
Order By: Relevance
“…In addition to differing in the criteria for what was considered "high antioxidant content," the two studies, which had 10 spices in common, also demonstrated a wide range of values for similar spices. For instance, the measured antioxidant content for chili powder and ground mustard seed were quite similar between Halvorsen et al's study and Dragland et al (10.5 mmol/100 g and 10.4 mmol/100 g) while the values for ground cinnamon were found to range from 17.7 mmol/100g in Halvorsen et al's study to 53.0 mmol/100g and 98.4 mmol/100g in Dragland et al's study (21,55). Dragland et al reported that antioxidant content of plants can differ between related varieties of plants, such as Mexican and Greek oregano, as well as growing seasons, which may also explain some of the variations in antioxidant content between similar spices in the two studies (21).…”
Section: Health Effectssupporting
confidence: 66%
See 3 more Smart Citations
“…In addition to differing in the criteria for what was considered "high antioxidant content," the two studies, which had 10 spices in common, also demonstrated a wide range of values for similar spices. For instance, the measured antioxidant content for chili powder and ground mustard seed were quite similar between Halvorsen et al's study and Dragland et al (10.5 mmol/100 g and 10.4 mmol/100 g) while the values for ground cinnamon were found to range from 17.7 mmol/100g in Halvorsen et al's study to 53.0 mmol/100g and 98.4 mmol/100g in Dragland et al's study (21,55). Dragland et al reported that antioxidant content of plants can differ between related varieties of plants, such as Mexican and Greek oregano, as well as growing seasons, which may also explain some of the variations in antioxidant content between similar spices in the two studies (21).…”
Section: Health Effectssupporting
confidence: 66%
“…This study found that of the top 50 foods with antioxidants, the top five antioxidants were dried spices (ground cloves, dried oregano, ground ginger, ground cinnamon, turmeric powder); however, compared to other categories of food products within this study, herbs and spices displayed the largest range in antioxidant capacity, 0.803-125.549 mmol/100 g (55). Another concern with these findings is that Halvorsen et al reported the antioxidant content as mmol/100 g, and even though data on the population-level exposure to herbs and spices is lacking, it would be much more unlikely a person would consume similar volumes of herbs and spices as they would other food categories reported in this study which were found to contain lower antioxidant levels but which are generally consumed in larger quantities on a regular basis, such as cereals and grains or fruits and vegetables (55).…”
Section: Health Effectsmentioning
confidence: 62%
See 2 more Smart Citations
“…Almost without exception, cooking increases the antioxidant content of foods. 49 Pycnogenol is a commercial preparation of polyphenolic compounds that has been extensively investigated, is well standardized and improves erectile function at a dose of 80-120 mg per day. 50 Ginseng has also been shown in a randomized trial to improve ED compared with placebo.…”
Section: Excessive Alcoholmentioning
confidence: 99%